COMPARATIVE STUDY OF DIFFERENT METHODS OF HYDROLYSIS AND FERMENTATION FOR BIOETHANOL OBTAINING FROM INULIN AND INULIN RICH FEEDSTOCK - Camelia (Bonciu) Neagu; Gabriela Bahrim (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Bioethanol serves as liquid fuel or gasoline enhancer in many countries in response to the progressive depletion of the world’s energetic resources. Production of bioethanol from inulin rich raw materials has been a subject of great interest for many years due to the large amount of existing and not completely developed technologies. The aim of this work was to study three different methods for hydrolysis and fermentation of pure inulin and Jerusalem artichoke flour: separate hydrolysis by A. niger MIUG 1.15 strain as active producer of inulinase, in stationary phase and under agitation, followed by fructose fermentation and simultaneous hydrolysis and fermentation of inulin and Jerusalem artichoke flour respectively, in order to increase the yield of biotransformation of substrate into ethanol. The highest amount of ethanol was formed during simultaneous hydrolysis and fermentation, for both pure inulin and Jerusalem artichoke (Helianthus tuberosus) tubers used as raw materials, of 16.2 g∙L-1 and 28.1 g∙L-1 respectively.